Secondary Labor in the Meatpacking Industry: Demographic Change and Student Mobility in Rural Iowa Schools - Mark A. Grey (Journal of Research in Rural Education, 1997)
This article addresses the relationship between dual labor markets and rural schools in Iowa. Particular attention is paid to the demographic transformation ofschool districts in rural communities that host large meatpacking plants. Most meatpacking jobs are secondary sectorjobs because they offer low wages and experience high injury rates and worker turnover. The industry'S ability to maintain these jobs depends on its ability to recruit sufficient workers to occupy them. As a result, meatpacking has become increasingly dependent on immigrant and refugee workers. The dependence on these workers has two consequences. Thefirst is that enrollments ofnon-English speaking students climb in rural schools that previously had little or no experience with minority and limited-English speaking populations. The second consequence is that employee turnover in the plants is reflected in school enrollment patterns. In order to illustrate this first situation, data from every rural Iowa school district associated with a large meatpacking plant are used. To illustrate the point about enrollment turnover, a case study from one community is used.